2018
DOI: 10.1016/j.aller.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Cross-over clinical trial for evaluating the safety of camel's milk intake in patients who are allergic to cow's milk protein

Abstract: Camel's milk is safe and tolerable in patients above one year of age with CMPA and can be considered as a good alternative given the benefit of its taste compared to other formulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The present study demonstrates that camel milk may be a suitable alternative to hypoallergenic infant formulas for CMA infant, as the low cross-reactivity should confer the camel milk low risk of inducing reactions. This is consistent with human studies showing that the introduction of camel milk to children with confirmed CMA, who did not respond to the conventional management, had a positive, rapid and long-lasting effect on their health [20,38]. Other studies have shown that neither camel milk caseins nor whey proteins could inhibit or bind to sera antibodies from patients with confirmed CMA [8,39].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The present study demonstrates that camel milk may be a suitable alternative to hypoallergenic infant formulas for CMA infant, as the low cross-reactivity should confer the camel milk low risk of inducing reactions. This is consistent with human studies showing that the introduction of camel milk to children with confirmed CMA, who did not respond to the conventional management, had a positive, rapid and long-lasting effect on their health [20,38]. Other studies have shown that neither camel milk caseins nor whey proteins could inhibit or bind to sera antibodies from patients with confirmed CMA [8,39].…”
Section: Discussionsupporting
confidence: 85%
“…Rastani et al [13] showed that CMA patients did not recognise camel milk by immunoblotting and concluded that camel milk is a promising alternative to cow’s milk for infant formula manufacture. Further, based on double-blind, placebo-controlled food challenges, Navarre-Rodriguez et al [20] concluded that camel milk is a safe and tolerable alternative for CMA patients above the age of one year. Camel milk is already commercially available in the Middle East, Australia, United Kingdom and the Netherlands [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the DRACMA guidelines of the World Allergy Organisation from 2010 recommend milk of other mammalians for individual patients when diagnostic indicates that they are tolerated [11]. Moreover, recent research has found camel's milk to be safe and well tolerated in patients with CMA over one year of age [30]. Both may explain the difference in opinion.…”
Section: Discussionmentioning
confidence: 99%
“…2018; Navarrete‐Rodríguez et al . 2018). Milk has antimicrobial activities against Gram‐positive and Gram‐negative bacteria.…”
Section: Introductionmentioning
confidence: 99%